THE EFFECTIVENESS OF FIRST TREATMENT OF ANKLE INJURIES WITH PRICE ON THE LEVEL OF KNOWLEDGE OF PENCAK SILAT ATHLETES IN SURAKARTA - Anni Sekar Taji; Yuli Widyastuti; Cemy Nur Fitria (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2026)
Background: Pencak silat is an exercise that is generally carried out to improve physical, technical and mental skills as well as the ability to injure in sports. The increase in injury incidence in Indonesia in 2018 was 9.2% and in Surakarta by 30.8%. One non-pharmacological treatment for early treatment when an ankle sprain occurs is to use the Protect, Rest, Ice, Compression, Elevation (PRICE) technique. Objective: To determine the effectiveness of early treatment of ankle injuries with PRICE on the level of knowledge of pencak silat athletes in Surakarta. Method: This research used a quasi-experimental design with one group pretest-posttest. With a total of 31 respondents and a questionnaire from Fajar Robin Pinanditto. The analysis test uses the Wilcoxon Signed Rank Test. Results: This research shows that the majority of athletes aged 13 years are 9 people (29.0%), 19 people are female (61.3%), and 17 people have junior high school education (54.8%). Initial treatment training for ankle injuries with PRICE is effective on the level of knowledge of pencak silat athletes in Surakarta with Asymp scores. signature. (2-tailed) 0.000. Conclusion: Training on the first treatment of ankle injuries with PRICE is effective on the level of knowledge of pencak silat players in Surakarta.